Bahasa sebagai Representasi Kekuasaan dalam Analisis Wacana Kritis Teks Politik - Fitri Damayanti; Siti Nurjanah (Journal of Language Studies, 2026)
This study investigates how language functions as a medium of power representation within political texts through the perspective of Critical Discourse Analysis (CDA). Political discourse often embeds ideological structures that influence public perception, construct dominance, and legitimize authority. The purpose of this research is to analyze linguistic features and discursive strategies used in selected political speeches to uncover implicit power relations. Utilizing a qualitative descriptive design, this study adopts Fairclough’s three-dimensional CDA framework, focusing on textual analysis, discourse practice, and sociocultural context. Data were collected from three political speeches delivered during national political events in Indonesia and were analyzed through coding, thematic classification, and interpretive discourse analysis. Findings indicate that lexical choices, modality, metaphors, and intertextuality are strategically employed to naturalize political ideologies, strengthen authority, and shape collective identities. The study concludes that political texts do not merely communicate information but actively construct and maintain power structures. These findings highlight the importance of CDA in fostering critical awareness of language use in political communication and encourage further research on multimodal political discourse.